Предмет: Алгебра,
автор: Gafkyi
упростить выражение (a-b)(a+b)-2(a²-b²)
Ответы
Автор ответа:
1
Вроде так
Это уже с сокращениями
Это уже с сокращениями
Gafkyi:
Нет
Автор ответа:
7
(а-в)(а+в)-2(а^2-в^2)=
(а^2-в^2)-2(а^2-в^2)=
Вынесем за скобки выражение (а^2-в^2)
Получим:
(а^2-в^2)(1-2)=
-1*(а^2-в^2)= -а^2+в^2
Ответ: -а^2+в^2.
(а^2-в^2)-2(а^2-в^2)=
Вынесем за скобки выражение (а^2-в^2)
Получим:
(а^2-в^2)(1-2)=
-1*(а^2-в^2)= -а^2+в^2
Ответ: -а^2+в^2.
Похожие вопросы
Предмет: Қазақ тiлi,
автор: rdanik2007
Предмет: Қазақ тiлi,
автор: danyskapur09
Предмет: Русский язык,
автор: oleg18365
Предмет: Литература,
автор: Аноним